"That's not what we do": Evidence that normative change is a mechanism of action in group interventions. (February 2015) - Cruwys, Tegan; Haslam, S. Alexander; Fox, Nicole E.; McMahon, Hayley
Abstract: Group interventions for mental health have proved very effective, but there is little consensus on their mechanism of action. In the present study, we posit that normative change is a plausible mechanism and provide a test of this in an eating disorder prevention group program. Participants were 112 women aged 15–25 years with body, shape or weight concerns who completed five questionnaires across the four session group-based intervention. Results indicated that participants experienced a significant reduction in thin-ideal internalization, body dissatisfaction and dieting intentions across the course of the program. These decrements were preceded by changes in group norms. Changes in both descriptive norms and injunctive norms in the first half of the program predicted improvement in thin-ideal internalization, body dissatisfaction and dieting intentions in the second half. Implications for theoretical models of attitude change are discussed, as well as implications for group interventions more generally. Highlights: Group psychotherapy creates an ideal environment for normative influence. This study examines normative influence in an eating disorder prevention group. Change in descriptive norms preceded change in correlates of disordered eating. Changes in descriptive and injunctive norms predicted intervention efficacy. Social mechanisms of action warrant more attention in group psychotherapy research.